As desigualdades multiplicadas - François Dubet (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2001)
Our societies are dominated by a fundamental contradiction: asdemocratic societies, they affirm the essential equality of all subjects butas capitalist societies they do notcease to construct markets which establish hierarchies of competenceand merit. This contradictionappears to increase rather thandiminish. How is it possible toreconcile equality for all and individual merit? Social movements arecreated which demand the recognitionof individuals independent of merit and a principle of equality that iseasily converted into blame, contemptand violence. Without abandoning thesearch for equality, the double nature of our societies requires that weestablish a policy for the recognitionof the subject.